Sistem, Informasi, Pegawai, Webs Sistem Informasi Pegawai Pada Kecamatan Pagar Alam Selatan Berbasis Web - sasmita (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2020)
The purpose of this research is to produce an employee information system in South Pagar Alam Subdistrict based on web that can make it easier for the Subdistrict to manage data and also facilitate those who want to get information quickly, and can be accessed anytime and anywhere. In the Sub-District Office of South Pagar Alam Subdistrict, Pagar Alam City, information about the Office is currently still manual, that is still using in the form of a ledger or file print out, and where in searching data is still manually so the data sought requires a long time. Data collection methods in this study use the method of interview, observation, documentation, and literature study. The system development method uses the waterfall method with stages of analysis, design, coding and testing. This system was developed using the Adobe Dreamweaver CS3, PHP, MySql, and Xampp applications. The results of the interim research in the form of employee information system in the District of Pagar Alam Selatan Web-Based. System testing uses usability testing with an average value of 4.63 which means that the user states that this website can facilitate the South Pagar Alam Subdistrict to convey information and also facilitate parties who want to get information quickly, and can be accessed anytime and anywhere only.